Rapid-cycle evaluation and learning for the effective delivery of integrated interventions in early childhood in rural India - Gaidhane, Abhay; Telrandhe, Shital; Patil, Manoj; Holding, Penny A.; Khatib, Mahalaqua Nazli; Gaidhane, Shilpa; Quazi Syed, Zahiruddin; Choudhari, Sonali G.; Umate, Roshan; Pathade, Aniket (Frontiers in Public Health, 2023)
Background: Effective and real-time data analytics play an essential role in understanding gaps and improving the quality and coverage of complex public health interventions. Studies of public health information systems identify problems with data quality, such as incomplete records and untimely reporting. Effective data collection and real-time analysis systems for rapid cycle learning are necessary to monitor public health programs and take timely evidence-based decisions. Early Childhood Development (ECD) programs are very diverse. Rapid cycle evaluation and learning (REAL) guides the implementation process of such complex interventions in real time. Stepping Stones was one such ECD program implemented in Central India. Objective: The objective was to improve the delivery of complex, integrated public health interventions for early childhood development in remote areas of rural India. Methodology: The program was developed according to principles of inclusion and community-centeredness, which can be tested quickly and iteratively. To enhance the decision-making process and improve delivery and coverage, the core team implemented an information system for rapid cycle learning. We developed performance indicators and a performance measurement matrix after defining the specific needs. Following that, we trained staff to collect complete data using electronic data collection tools and transfer it the same day to the server for quality review and further analysis. A variety of data/information was triangulated to address the gaps in intervention delivery and those decisions were subsequently implemented. Results: We observed that the quality of data collection improved, and errors were reduced by 50% in 3rd quarter. The quality of the narrative was also enhanced, it became elaborate and reflective. Sharing their field output in meetings and improving the quality of the narrative enhanced the self-reflection skills of field staff and consequently improved the quality of intervention delivery. Refresher training and mentoring by supervisors helped to improve the data quality over time. Conclusion: Rapid-cycle Evaluation And Learning (REAL) can be implemented in resource-limited settings to improve the quality and coverage of integrated intervention in early childhood. It nurtures a reinforcing ecosystem that integrates providers, community, and family perspectives and guides interactions among stakeholders by integrating data from all available sources.